Impact of Saharan dust episodes on preterm births in Guadeloupe (French West Indies). Issue 5 (18th March 2019) - Viel, Jean-Francois; Mallet, Yoann; Raghoumandan, Christina; Quénel, Philippe; Kadhel, Philippe; Rouget, Florence; Multigner, Luc
Abstract : Objectives: Large amounts of mineral dust are transported from their African sources in the Saharan-Sahel region to the Caribbean Sea, generating peak exposures to particulate matter ≤10 µm (PM10 ). This study aimed to investigate the impact of Saharan dust episodes on preterm births in the Guadeloupe archipelago. Methods: The study population consisted of 909 pregnant women who were enrolled in the TIMOUN mother-child cohort between 2004 and 2007. Desert dust episodes were assessed from PM10 concentrations recorded at the unique background air quality monitoring station located in Pointe-à-Pitre. For each woman, the daily PM10 concentrations were averaged over the entire pregnancy, and the proportion of days with intense dust episodes (≥55 µg PM10 /m 3 ) during pregnancy was calculated. Weighted logistic regression models adjusting for known individual sociomedical risk factors were used to estimate ORs and 95% CIs for preterm birth. Results: During pregnancy, the mean PM10 concentrations ranged from 13.17 to 34.92 µg/m 3, whereas the proportion of intense dust events ranged from 0.00% to 19.41%. Increased adjusted ORs were found for both the mean PM10 concentrations and the proportion of intense dust events (OR 1.40, 95% CI 1.08 to 1.81, and OR 1.54, 95% CI 1.21 to 1.98 per SD change, respectively). Restriction to spontaneous preterm births produced similar ORs but with wider 95% CIs. Conclusion: Considering the personal and social burden of this adverse pregnancy outcome, this finding is of importance for both healthcare workers and policy makers to provide necessary preventive measures.